Hydration and durability of low-heat cementitious composites for dam concrete: Thermodynamic modeling and experiments - Zhang, Juntao; Lv, Tong (Frontiers in Materials, 2023)
To demonstrate the superiority of dam concrete, a systematic study is conducted in this paper regarding the durability of low heat cementitious composite (LHCC) that is comprised of Portland cement (PC), fly ash (FA) and MgO expansive additive (MEA), with PC as the reference group. Furthermore, through GEMS software, XRD, SEM and EDS, the mechanism of difference in durability between the two cementitious materials is revealed from the perspectives of phase evolution and microstructural characteristics. 40 ℃ water curing is adopted in the study so as to match the long-term temperature field inside the concrete dam. According to the results of RCM experiment, accelerated carbonation experiment and rapid freezing-thawing cycle experiment, LHCC outperforms PC in durability. The hydration process of LHCC is simulated by inputting the reaction degree of each phase calculated by using MPK model into GEMS software. The output thermodynamic model shows that portlandite first increases and then decreases as LHCC hydration proceeds, and C-S-H and stratlingite are obviously supplemented in the later stage, which reflects the high performance of FA involved in hydration. Besides, hydrotalcite capable of chloride ion adsorption is increasing generated with the consumption of brucite. As shown clearly in SEM images, there are denser space grids formed by overlapping C-S-H in LHCC, with almost no capillary pores. Meanwhile, combined with the results of EDS, it is strongly demonstrated that the FA in LHCC can be hydrated to produce dense fibrous C-S-H in large amounts, providing a basis for the positive development of durability.